Teachers' Challenges on the Implementation of the Merdeka Curriculum for Coastal Children - Mahsya Aura Zerlinda; Naufal Ahmad Rijalul Alam (JIE (Journal of Islamic Education), 2025)
This research focuses on teachers' challenges in implementing the Merdeka Curriculum in coastal areas, especially at State Senior High School 3 Cilacap, in the context of coastal children's education. The Merdeka Curriculum is an education policy that provides flexibility in learning by optimising local potential and strengthening character. This research uses a qualitative approach with a case study design. The data is collected through in-depth interviews, observation, and documentation. The data collection technique used the triangulation method to ensure the accuracy and richness of the information obtained. Data validity was guaranteed through matching research findings with the reality observed by researchers in the field. Data analysis was conducted using the thematic method, which enabled the researcher to identify key themes from the interviews and documentation. These themes include the main challenges in teachers' understanding of the curriculum, limited educational resources, and efforts to integrate local potential into learning. The results show that implementing the Merdeka Curriculum in coastal areas faces various obstacles, such as low teacher understanding and challenging geographical conditions. However, environment-based programs, such as mangrove planting, have significantly strengthened students' character and ecological awareness. This research confirms the need for close collaboration between schools, government, and communities to overcome teachers' challenges and maximise the benefits of the Merdeka Curriculum in coastal areas.